A pH-sensitive eosin-block copolymer delivers proteins intracellularly. Issue 91 (28th October 2020) - Reinhard, Sören; Han, Hesong; Tuma, Jan; Røise, Joachim Justad; Li, I-Che; Li, Jie; Lee, Hye Young; Murthy, Niren
Abstract : An acid-hydrolyzable PEG-poly-eosin polymer (PEG-pEosin) complexes and shields proteins reversibly and delivers proteins intracellularly. In vivo gene editing in mouse brains is shown. Abstract : There is great interest in developing strategies to deliver proteins into the cytoplasm of cells. We report here a PEG-poly-eosin block copolymer (PEG-pEosin) that can encapsulate proteins and release them in active form under mildly acidic conditions. A PEG-pEosin formulation composed of Cre and the endosomolytic protein LLO efficiently performed gene editing in cells and in the brains of mice after an intracranial injection.